Moderating impact of perceived organizational support toward burnout on work engagement in Nurses - Kezia Riventa Talumepa; Hana Panggabean (University of Merdeka Malang, 2022)
Nurses work at the frontline with high intensity in patient care, especially handling the COVID-19. Work pressure and stress faced by nurses can increase burnout (BO) as a syndrome of emotional exhaustion that occurs over a long period of time. One of the negative impact of burnout is the decrease in work engagement (WE). The presence of perceived organizational support (POS) has been shown to be correlated with low BO, and in turn, is correlated with high level of WE. This study aims to examine the contribution of BO to WE moderated by POS for nurses at the Hospital Prof R.D. Kandou in North Sulawesi as a referral COVID-19 hospital. This study involved 111 nurses from isolation room and emergency room using the convenience sampling technique. Data analysis was conducted using the moderation analysis with the help of JASP software. From the result, indicate that BO significantly affect WE which give a 26.9% contribution. POS adds contribution when together with BO its affects WE by 27.8%, to 54.7%. The results of the study show that POS significantly moderates the effect of BO on WE.Keywords: burnout; COVID-19; nurses; perceived organizational support; work engagement